2015
DOI: 10.1186/s12893-015-0105-2
|View full text |Cite
|
Sign up to set email alerts
|

A solution to the negative effects of splenectomy during colorectal trauma and surgery: an experimental study on splenic autotransplantation to the groin area

Abstract: BackgroundSplenectomy after combined colosplenic trauma or iatrogenic splenic injury during colorectal surgery associates with worse short- and long-term outcomes, including reduced survival in patients with colorectal cancer. Splenic autotransplantation may improve the outcomes of such patients. Omental splenic transplantation is the standard procedure but may be difficult when performing laparoscopic colorectal surgery or when total or subtotal omentectomy is required. This animal model study was performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Anastomotic leaks requiring surgery were observed most frequently following splenectomy (7.9%) but this was significantly lower following spleen preservation (3.3%, P=0.003). An association of splenectomy with impaired anastomotic healing has been reported in animal studies and may explain the increased risk of peri-operative morbidity that we observed (18). Wang (11,12).…”
Section: Discussionsupporting
confidence: 64%
“…Anastomotic leaks requiring surgery were observed most frequently following splenectomy (7.9%) but this was significantly lower following spleen preservation (3.3%, P=0.003). An association of splenectomy with impaired anastomotic healing has been reported in animal studies and may explain the increased risk of peri-operative morbidity that we observed (18). Wang (11,12).…”
Section: Discussionsupporting
confidence: 64%
“… Group 2 (hepatectomy): using the partial hepatectomy technique described by Higgins and Anderson [ 9 ], the right medial, left medial and left lateral lobes were resected in a 70% hepatectomy. Group 3 (splenectomy): the splenic vein and artery were ligated using a 4/0 polyglactin suture (Vicryl, Ethicon Endo-Surgery, Cincinnati, USA) for the splenectomy [ 10 ]. Group 4 (nephrectomy): nephrectomy was performed with the isolation of the renal hilum and ligation of the right renal artery to the ureter using a 4/0 polyglactin suture (Vicryl, Ethicon Endo-Surgery, Cincinnati, USA) [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Group 3 (splenectomy): the splenic vein and artery were ligated using a 4/0 polyglactin suture (Vicryl, Ethicon Endo-Surgery, Cincinnati, USA) for the splenectomy [ 10 ].…”
Section: Methodsmentioning
confidence: 99%